Spatiotemporal Evolution of Mountainous Ecosystem Services in an Arid Region and Its Influencing Factors: A Case Study of the Tianshan Mountains in Xinjiang - Yayan Lu; Xiaoliang Xu; Junhong Zhao; Fang Han (Land, 2022)
Mountainous ecosystems provide humans with multiple ecosystem services (ESs), but global changes and anthropogenic activities threaten the supply of such services in arid regions. To maintain regional ecological security and achieve ecosystem sustainability, it is quite essential to understand the spatiotemporal characteristics of mountainous ESs in arid regions and clarify the main driving factors of different ESs. Using the integrated valuation of ecosystem services and tradeoffs (InVEST) and revised universal soil-loss equation (RUSLE) models, we evaluated the ESs provided by the Tianshan Mountains of Xinjiang from 2000 to 2020. The research showed that: (i) over the 20 years in question, habitat quality and carbon storage remained relatively stable, while soil retention and water yield fluctuated significantly. (ii) All ES pairs exhibited synergies. Spatial synergy areas were concentrated in the northwestern and southwestern areas; spatial trade-off areas alternated with spatial synergy areas. (iii) Hotspots with at least two ESs covered 73% of the study region. Middle- and high-altitude areas were the main supply areas of ES. (iv) Land-use types were the dominant driving factor of habitat quality and carbon storage, while mean annual precipitation had the strongest explanatory power for water yield. Soil retention was mainly affected by mean annual temperature and the normalized difference vegetation index. Our findings could provide guidance for policymakers when developing measures for ecosystem conservation and management.